Towards compartmentalized photocatalysis: multihaem proteins as transmembrane molecular electron conduits. (10th April 2019) - Stikane, Anna; Hwang, Ee Taek; Ainsworth, Emma V.; Piper, Samuel E. H.; Critchley, Kevin; Butt, Julea N.; Reisner, Erwin; Jeuken, Lars J. C.
Abstract : We show a proof-of-concept for using MtrCAB as a lipid membrane-spanning building block for compartmentalised photocatalysis that mimics photosynthesis. Abstract : The high quantum efficiency of natural photosynthesis has inspired chemists for solar fuel synthesis. In photosynthesis, charge recombination in photosystems is minimized by efficient charge separation across the thylakoid membrane. Building on our previous bioelectrochemical studies of electron transfer between a light-harvesting nanoparticle (LHNP) and the decahaem subunit MtrC, we demonstrate photo-induced electron transfer through the full transmembrane MtrCAB complex in liposome membranes. Successful photoelectron transfer is demonstrated by the decomposition of a redox dye, Reactive Red 120 (RR120), encapsulated in MtrCAB proteoliposomes. The photoreduction rates are found to be dependent on the identity of the external LHNPs, specifically, dye-sensitized TiO2, amorphous carbon dots (a-CD) and graphitic carbon dots with core nitrogen doping (g-N-CDs). Agglomeration or aggregation of TiO2 NPs likely reduces the kinetics of RR120 reductive decomposition. In contrast, with the dispersed a-CD and g-N-CDs, the kinetics of the RR120 reductive decomposition are observed to be faster with the MtrCAB proteoliposomes and we propose that this is due to enhancement in the charge-separated state. Thus, we show a proof-of-concept for using MtrCAB as a lipid membrane-spanning building block for compartmentalised photocatalysis that mimics photosynthesis. Future work is focused on incorporation of fuel generating redox catalysts in the MtrCAB proteoliposome lumen.